∣ ∣ ∣ ∣ ( 2 − i 1 + i ) 3 + i ∣ ∣ ∣ ∣ = a e − π / b
The expression above holds true for positive integers a and b , where a is square free.
Find the value of 6 3 a 3 b .
Notations :
Hint : Euler's Formula is the core of this problem.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
e 4 π = e 4 π i although e 4 π i = cos 4 π + i sin 4 π . e 4 π is simply e 4 π . Excuse my LaTeX
Problem Loading...
Note Loading...
Set Loading...
∣ ( 2 − i 1 + i ) 3 + i ∣
= ∣ ( 1 + i ) 2 − i 3 + i ∣
= ∣ ( 1 + i ) 2 − i 3 + i × 2 + i 2 + i ∣
= ∣ ( 1 + i ) 5 5 + 5 i ∣
= ∣ ( 1 + i ) 1 + i ∣
= ∣ ( 2 e 4 π i ) 1 + i ∣
= ∣ ( 2 e 4 π i ) ( ( 2 ) i e − 4 π ) ∣
= ∣ ( 2 e − 4 π ) ( ( 2 ) i e 4 π i ) ∣
= ∣ ( 2 e − 4 π ) ( e ( ln 2 + 4 π ) i ) ∣
= ( 2 e − 4 π ) ∣ ( e ( ln 2 + 4 π ) i ) ∣
= ( 2 e − 4 π ) ( 1 )
= ( 2 e − 4 π )
⇒ 6 3 a 3 b = 6 3 ( 2 ) 3 ( 4 ) = 2 0 1 6
e 4 π = cos ( 4 π ) + i sin ( 4 π )
e 4 π = 2 2 + i 2 2
( 2 ) e 4 π = ( 2 ) 2 2 + ( 2 ) i 2 2
2 e 4 π = 1 + i
∣ e i x ∣ = cos ( x ) 2 + sin ( x ) 2
∣ e i x ∣ = 1
⇒ ∣ ( e ( ln 2 + 4 π ) i ) ∣ = 1